Evaluating the role of digital media in language development among pre-schoolers: An observational study - Ramisetty Uma Mahesh; Tumati Kedarnath Reddy; Haarika V; Chandra Sekhar G (Asian Journal of Medical Sciences, 2024)
Background: Digital media consumption is prevalent among pre-schoolers, but its impact on language development remains unclear. Aims and Objectives: This study investigates the effects of different types of digital media on pre-school children’s language outcomes. Materials and Methods: A total of 100 pre-school-aged children (mean age 4.2±0.5 years; 51% male) were observed for 12 months. Digital media exposure was categorized into educational interactive, educational passive, and non-educational content, with average screen time being 1.5±0.45 h daily. Language development was assessed using the Preschool Language Scale-5 (PLS-5) at baseline and 12-month follow-up. Results: At the 12-month follow-up, the study participants exhibited an average Total Language Score (TLS) increase from 100±10 to 107±12. Interactive educational app users showed significant language improvements (TLS: 112±10; P<0.05), exceeding gains seen in passive educational (TLS: 104±10) and non-educational content users (TLS: 102±12). Vocabulary size, expressive language, and receptive language improvements were highest in the interactive group (20%, 15%, and 10%, respectively). Behavioral assessments indicated enhanced use of complex sentences and turn-taking skills in the interactive group. Parental co-viewing correlated with higher TLS gains across all groups, with the most pronounced benefit in the interactive group (9 points vs. 6 without co-viewing). Interactive app users also exhibited higher cognitive (40%) and emotional engagement. Conclusion: Our study emphasizes the positive influence of interactive educational apps on pre-schoolers’ language development, with notable gains and augmented outcomes through parental involvement. This highlights the value of guided media use in early childhood education.